A long-life magnesium-vanadium tetrasulfide battery
Patent Information
- Application Number
- CN202611231948.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-14
- Publication Date
- 2026-10-30
AI Technical Summary
然而,这种基于多电子氧化还原反应的高容量输出,往往伴随着充放电过程中剧烈的晶格收缩膨胀和不可逆相变,极易引发电极材料的结构退化甚至粉化,导致循环稳定性急剧下降
[0017]本发明有益效果包括:本发明通过正极材料微观结构设计与电解液添加剂工程的有效结合,成功开发了一种兼具高比容量和超长循环寿命的镁-四硫化钒电池。其中,海葵状VS4(海葵状四硫化钒)正极材料中纳米棒根部聚集、尾部发散的独特结构,既提供了丰富的电化学活性位点以实现高达250mAh·g-1的优异比容量,又借助纳米棒根部紧密聚集的结构特征赋予了电极材料抵抗晶格应变的结构稳定性;与此同时,电解液中吡咯烷/铵盐类添加剂的引入,通过在VS4层间的插层作用有效扩大了层间距并屏蔽了Mg2+与基体间的强静电相互作用,显著改善了Mg2+的扩散动力学;此外,电解液中氯化铟添加剂的引入,通过在镁表面原位生成亲镁的活性位点,引导Mg2+实现平坦、致密的镁沉积,显著提升了电池的循环寿命。三者协同作用,使得本发明镁-四硫化钒电池在2A·g-1的大电流密度下经25000次循环后容量保持率仍高达61.6%。
Smart Images

Figure CN123018090A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of magnesium batteries, specifically relating to a long-life magnesium-vanadium tetrasulfide battery. Background Technology
[0002] Magnesium-ion batteries, with their abundant resources, small ionic radius, and higher theoretical volumetric capacity, are considered one of the most promising electrochemical energy storage systems for large-scale energy storage. Furthermore, the magnesium metal anode is less prone to dendrite formation during operation, effectively avoiding safety hazards such as thermal runaway caused by lithium dendrites piercing the separator in lithium-ion batteries, significantly improving battery safety. Despite these advantages, the scarcity of high-performance cathode materials and the lack of compatible electrolytes hinder the development of magnesium batteries with high specific power, high specific energy, and long cycle life, severely restricting their commercial application.
[0003] In terms of cathode materials, existing technologies document various magnesium-ion battery cathode material systems, including Chevrel phase materials (such as Mo6S8), layered transition metal oxides (such as V2O5, MnO2), polyanionic compounds (such as MgFeSiO4), layered transition metal sulfides (such as TiS2), and organic compounds (such as PTCDA). However, the magnesium storage mechanism of most of these candidate materials mainly relies on the redox reaction of a single cation, which can only achieve single or double electron transfer, thus fundamentally limiting the potential for improving specific capacity. VS4 (vanadium tetrasulfide), due to its unique "one-dimensional atomic chain" structure, exhibits multi-electron transfer characteristics with co-valence changes of anions and cations during battery operation, thus endowing the electrode material with a theoretical specific capacity far exceeding that of traditional cathode materials, and has attracted widespread attention in recent years. However, this high capacity output based on multi-electron redox reactions is often accompanied by drastic lattice contraction and expansion and irreversible phase transitions during charge and discharge, which can easily lead to structural degradation or even pulverization of the electrode material, resulting in a sharp decline in cycle stability.
[0004] In addition to the structural instability of the cathode material itself, magnesium-ion batteries face another fundamental kinetic obstacle. This is because Mg... 2+ With its small ionic radius and high charge density, Mg exhibits extremely strong electrostatic interactions with the cathode material's crystal framework, leading to... 2+ The migration rate of Mg in the host material is extremely slow, and the intercalation and deintercalation processes require overcoming a high activation energy barrier, severely affecting the reaction kinetics and rate performance of the electrode material. This strong electrostatic effect results in the actual capacity of most traditional cathode materials in magnesium batteries being far lower than their theoretical values, with particularly severe capacity decay at high current densities. Therefore, how to weaken the electrostatic effect of Mg... 2+Maintaining the structural integrity of the electrode material during long-term cycling while improving diffusion dynamics through electrostatic interaction with the substrate is also a key technical issue in overcoming the performance bottleneck of magnesium batteries. Summary of the Invention
[0005] Therefore, the present invention aims to provide a long-life magnesium-vanadium tetrasulfide battery, which mainly consists of anemone-shaped vanadium tetrasulfide (VS4) and pyrrolidine / ammonium salt additives. The synergistic effect of these two components enables the magnesium-vanadium tetrasulfide battery to achieve a lifespan of 2 A·g. -1 Even after 25,000 cycles at high current density, the capacity retention rate is still as high as 61.6%.
[0006] To achieve the above objectives, the present invention can adopt the following technical solutions:
[0007] This invention provides a long-life magnesium-vanadium tetrasulfide battery, comprising a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte. The positive electrode contains anemone-shaped vanadium tetrasulfide, which is formed by multiple nanorods aggregated at the roots and diverging at the tails. The nanorods have a diameter of 10 nm to 30 nm and a length of 1 μm to 2 μm. The non-aqueous electrolyte comprises a magnesium battery electrolyte and electrolyte additives. The magnesium battery electrolyte is a Grignard reagent-based magnesium battery electrolyte. The electrolyte additives include electrolyte additives that act on the positive electrode and electrolyte additives that act on the negative electrode. The electrolyte additives that act on the positive electrode are selected from one or more combinations of 1-butyl-1-methylpyrrolidine chloride (PY14Cl), 1-butyl-1-methylpyrrolidine onium bromide (BMPyrrBr), hexadecyltrimethylammonium chloride (CTACl), or tetrabutylammonium chloride (TBACl). The electrolyte additives that act on the negative electrode are indium chloride.
[0008] Preferably, in the above-mentioned magnesium-vanadium tetrasulfide battery, the specific surface area of the anemone-shaped vanadium tetrasulfide is 20 m². 2 / g~50m 2 / g.
[0009] Preferably, the preparation method of the anemone-shaped vanadium tetrasulfide in the above magnesium-vanadium tetrasulfide battery includes: (1) dissolving ammonium metavanadate in N-methylpyrrolidone to obtain solution A; dissolving thioacetamide in anhydrous ethanol to obtain solution B; (2) mixing solution A and solution B to obtain solution C; (3) subjecting solution C to a solvothermal reaction to obtain anemone-shaped vanadium tetrasulfide.
[0010] Preferably, in the above-mentioned magnesium-vanadium tetrasulfide battery, the mass ratio of ammonium metavanadate to thioacetamide is 1:(2-4); and / or the volume ratio of N-methylpyrrolidone to anhydrous ethanol is 1:(0.8-1.2).
[0011] Preferably, in the above-mentioned magnesium-vanadium tetrasulfide battery, step (2) includes: mixing solution A and solution B for the first stirring, then mixing them for the second stirring to obtain solution C; the temperature of the first stirring is 50°C to 70°C and the time is 20 min to 40 min; the temperature of the second stirring is 20°C to 40°C and the time is 0.5 h to 2 h; and / or in step (3), the temperature of the solvothermal reaction is 150°C to 180°C and the reaction time is 20 h to 28 h.
[0012] Preferably, in the above magnesium-vanadium tetrasulfide battery, in step (3), after the solution C undergoes a solvothermal reaction, it is centrifuged, the precipitate is washed, and dried to obtain anemone-shaped vanadium tetrasulfide powder; wherein, the washing includes: washing with deionized water and anhydrous ethanol at least three times in sequence; and / or the drying is vacuum drying, the drying temperature is 60°C to 100°C, and the drying time is 10h to 14h.
[0013] Preferably, in the above-mentioned magnesium-vanadium tetrasulfide battery, the Grignard reagent-based magnesium battery electrolyte is selected from APC electrolyte (phenyl magnesium chloride-aluminum trichloride / tetrahydrofuran complex electrolyte), phenoxy magnesium chloride-aluminum chloride complex electrolyte, or magnesium aluminum chloride complex electrolyte.
[0014] Preferably, in the above-mentioned magnesium-vanadium tetrasulfide battery, the solvent of the non-aqueous electrolyte is selected from one or more combinations of tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, or tetraethylene glycol dimethyl ether.
[0015] Preferably, in the above-mentioned magnesium-vanadium tetrasulfide battery, the concentrations of the electrolyte additives acting on the positive electrode and the electrolyte additives acting on the negative electrode in the non-aqueous electrolyte are independently 0.1 mol / L to 0.5 mol / L.
[0016] Preferably, in the above-mentioned magnesium-vanadium tetrasulfide battery, the positive electrode further includes a conductive agent and a binder. The conductive agent is one or more combinations of conductive carbon black, conductive graphite, carbon nanotubes, or graphene, and the binder is polyvinylidene fluoride (PVDF). The mass ratio of the magnesium-based battery positive electrode material, the conductive agent, and the binder is (6-8):(1-3):1. The negative electrode is a magnesium foil negative electrode sheet or a magnesium alloy negative electrode sheet. The magnesium alloy is selected from one or more combinations of AZ31 magnesium alloy, magnesium gadolinium alloy, or magnesium cerium alloy.
[0017] The beneficial effects of this invention include: By effectively combining the microstructure design of the cathode material with the engineering of electrolyte additives, this invention has successfully developed a magnesium-vanadium tetrasulfide battery that possesses both high specific capacity and ultra-long cycle life. Specifically, the unique structure of the anemone-like VS4 (vanadium tetrasulfide) cathode material, with its nanorods clustering at the roots and diverging at the tails, provides abundant electrochemical active sites to achieve a capacity as high as 250 mAh·g. -1The excellent specific capacity, coupled with the tightly aggregated structure at the roots of the nanorods, endows the electrode material with structural stability to resist lattice strain. Simultaneously, the introduction of pyrrolidine / ammonium salt additives into the electrolyte effectively expands the interlayer spacing and shields Mg through intercalation between the VS4 layers. 2+ The strong electrostatic interaction between Mg and the matrix significantly improved the Mg 2+ The diffusion kinetics; furthermore, the introduction of indium chloride additives into the electrolyte guides the diffusion of Mg by generating magnesophilic active sites in situ on the magnesium surface. 2+ Achieving a flat and dense magnesium deposition significantly improves the cycle life of the battery. The synergistic effect of these three factors enables the magnesium-vanadium tetrasulfide battery of this invention to achieve a cycle life of 2 A·g. -1 Even after 25,000 cycles at high current density, the capacity retention rate is still as high as 61.6%. Attached Figure Description
[0018] Figure 1 X-ray diffraction pattern of the anemone-shaped vanadium tetrasulfide powder prepared in Example 1;
[0019] Figure 2 TEM image of the anemone-shaped vanadium tetrasulfide powder prepared in Example 1;
[0020] Figure 3 The coin cell assembled for Example 1 was tested at 50 mA·g. -1 Charge-discharge curves at current density;
[0021] Figure 4 The assembled coin cell for Comparative Example 1 was tested at 50 mA·g. -1 Charge-discharge curves at current density;
[0022] Figure 5 The coin cell assembled for Example 1 at 2A·g -1 Cyclic curves at current density;
[0023] Figure 6 The assembled coin cell for Comparative Example 1 was tested at 2 A·g -1 Cyclic curves at current density. Detailed Implementation
[0024] The embodiments described are provided to better illustrate the present invention, but are not intended to limit the scope of the invention to the embodiments described. Therefore, non-essential improvements and adjustments made to the embodiments by those skilled in the art based on the above description are still within the scope of protection of the present invention.
[0025] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit this disclosure. Singular expressions include plural expressions unless they have a distinct meaning in the context. As used herein, it should be understood that terms such as “comprising,” “having,” “including,” are intended to indicate the presence of features, numbers, operations, components, parts, elements, materials, or combinations thereof. The terminology of the invention is disclosed in the specification and is not intended to exclude the possibility that one or more other features, numbers, operations, components, parts, elements, materials, or combinations thereof may be present or added. As used herein, “ / ” may be interpreted as “and” or “or,” depending on the context.
[0026] This invention provides a long-life magnesium-vanadium tetrasulfide battery, comprising a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte. The positive electrode comprises anemone-shaped vanadium tetrasulfide, which is formed by multiple nanorods aggregated at their roots and diverging at their tails. The nanorods have a diameter of 10 nm to 30 nm and a length of 1 μm to 2 μm. The non-aqueous electrolyte comprises a magnesium battery electrolyte and electrolyte additives. The magnesium battery electrolyte is a Grignard reagent-based magnesium battery electrolyte. The electrolyte additives include an electrolyte additive that acts on the positive electrode and an electrolyte additive that acts on the negative electrode. The electrolyte additive that acts on the positive electrode is selected from one or more combinations of 1-butyl-1-methylpyrrolidine chloride (PY14Cl), 1-butyl-1-methylpyrrolidine onium bromide (BMPyrrBr), hexadecyltrimethylammonium chloride (CTACl), or tetrabutylammonium chloride (TBACl). The electrolyte additive that acts on the negative electrode is indium chloride.
[0027] It should be noted that the quaternary ammonium salt ionic liquid additive system of this invention can achieve ultra-long battery cycle life. Specifically, the additive cations for the positive electrode can be embedded in the VS4 interlayer, expanding the interlayer spacing and shielding Mg. 2+ Strong electrostatic forces significantly enhance the diffusion rate of magnesium ions; for the negative electrode, additive cations generate magnesium-affinity sites in situ on the magnesium surface, guiding Mg... 2+ Uniform distribution achieves flat and dense magnesium deposition, suppressing dendrite growth. The anemone-graded VS4 cathode, combined with a modified Pentair electrolyte, synergistically enhances performance. Co-valence variation of anions and cations provides high capacity, and additives optimize the interphase kinetics, achieving a capacity of 2 A·g. -1 Under high current, the capacity retention rate can reach 61.6% after 25,000 cycles, far exceeding that of additive-free batteries.
[0028] In addition, existing common blocky and disordered rod-shaped VS4 have defects: Mg 2+High charge density leads to violent lattice expansion and contraction during insertion and extraction, resulting in irreversible structural collapse and rapid decay of cycling capacity. Random particles also suffer from blocked internal channels, poor electrolyte wetting, and sluggish magnesium ion diffusion kinetics, relying solely on single-metal ion redox reactions, leading to lower theoretical and practical capacities. This invention constructs a hierarchical anemone-like microstructure with root aggregation and tail radiation, verified by TEM characterization. Furthermore, the anemone-like vanadium tetrasulfide nanorods in this invention can have diameters of 10nm, 15nm, 20nm, 25nm, or 30nm, and lengths of 1μm, 1.2μm, 1.5μm, 1.7μm, or 2μm. Multiple nanorods anchor and aggregate at the roots to form a stable framework, while the radial tails create numerous interconnected pores, offering the following advantages: ① Abundant pores significantly increase the electrolyte wetting area, shortening the Mg2+ diffusion time. 2+ ① Improved migration pathways and ion transport dynamics; ② The radial hierarchical structure provides an elastic buffer space, effectively mitigating charge-discharge lattice deformation and inhibiting particle pulverization and irreversible structural damage; ③ During material operation, V and S cations and anions participate in redox simultaneously, achieving multi-electron transfer and breaking through the capacity limit of traditional single-metal redox cathodes. Combined with a specific additive electrolyte system, a capacity of 50 mA·g is achieved. -1 The actual discharge specific capacity can reach 250 mAh·g -1 .
[0029] In some specific examples, the anemone-shaped vanadium tetrasulfide in the above-mentioned magnesium-vanadium tetrasulfide battery has a specific surface area of 20 m². 2 / g~50m 2 / g.
[0030] It should be noted that the specific surface area of the anemone-like vanadium tetrasulfide in this invention can be 20 m². 2 / g、25m 2 / g、30m 2 / g、35m 2 / g、40m 2 / g、45m 2 / g or 50m 2 / g, etc. If the specific surface area is less than 20m² 2 / g, insufficient number of electrochemically active sites, lack of magnesium ion insertion sites, and decreased discharge capacity; if higher than 50m 2 / g, the side reactions between the material surface and the electrolyte intensify, continuously consuming the electrolyte, resulting in self-discharge and long-cycle capacity decay. Specific surface area is controlled at 20m². 2 / g~50mm 2 / g can balance the number of active sites and the risk of interfacial side reactions, ensuring high discharge specific capacity while inhibiting continuous electrolyte decomposition, thus meeting the needs of long-cycle magnesium batteries.
[0031] In some specific examples, the preparation method of anemone-shaped vanadium tetrasulfide in the above magnesium-vanadium tetrasulfide battery includes: (1) dissolving ammonium metavanadate in N-methylpyrrolidone to obtain solution A; dissolving thioacetamide in anhydrous ethanol to obtain solution B; (2) mixing solution A and solution B to obtain solution C; (3) subjecting solution C to a solvothermal reaction to obtain anemone-shaped vanadium tetrasulfide.
[0032] It should be noted that this invention employs a dual-solvent controlled-form solvothermal route using NMP-anhydrous ethanol, with ammonium metavanadate as the vanadium source and thioacetamide for low-temperature sustained-release S. 2- Sulfur source, stepwise premixing to regulate precursor nucleation kinetics: NMP has strong polarity and fully dissolves the metal precursor; ethanol reduces the overall polarity of the system and induces crystals to grow in a one-dimensional direction; first, the vanadium-sulfur precursor is fully dissolved separately, and then the nucleation rate is slowly regulated by low-temperature compounding solvent to avoid instantaneous burst nucleation that leads to disordered particle aggregation; no high-temperature calcination is required throughout the process, and pure phase VS4 is synthesized in one solvothermal step without vanadium oxide impurities. The product has a uniform microstructure and can stably prepare hierarchical structures of anemone nanorods with root aggregation and tail divergence.
[0033] In some specific examples, in the preparation method of the anemone-shaped vanadium tetrasulfide in the above-mentioned magnesium-vanadium tetrasulfide battery, the mass ratio of ammonium metavanadate to thioacetamide is 1:(2-4).
[0034] It should be noted that the mass ratio of vanadium source to sulfur source can be selected as 1:2, 1:2.5, 1:3, 1:3.5 or 1:4, etc.; if the sulfur source ratio is less than 2, the sulfidation reaction will be incomplete, generating low-valence vanadium oxide impurities and reducing the purity of the active material; if the ratio is greater than 4, the excessive sulfur source will cause random agglomeration of particles and destroy the radioactive micromorphology of the sea anemone.
[0035] In some specific examples, in the preparation method of the anemone-shaped vanadium tetrasulfide in the above-mentioned magnesium-vanadium tetrasulfide battery, the volume ratio of N-methylpyrrolidone (NMP) to anhydrous ethanol is 1:(0.8~1.2).
[0036] It should be noted that the volume ratio of NMP to anhydrous ethanol can be 1:0.8, 1:0.9, 1:1, 1:1.1, or 1:1.2, etc. If the ethanol content is too low, the system polarity is too high, the anisotropic growth ability of crystals is weak, and the nanorods are short and have no radioactive structure. If the ethanol content is too high, the precursor will nucleate in large quantities instantaneously, the particles will be disordered and agglomerated, and it will be impossible to form the sea anemone skeleton that aggregates at the root.
[0037] In some specific examples, in the preparation method of the anemone-shaped vanadium tetrasulfide in the above magnesium-vanadium tetrasulfide battery, step (2) includes: mixing solution A and solution B for the first stirring, then mixing for the second stirring to obtain solution C; the temperature of the first stirring is 50°C to 70°C and the time is 20 min to 40 min; the temperature of the second stirring is 20°C to 40°C and the time is 0.5 h to 2 h; and / or in step (3), the temperature of the solvothermal reaction is 150°C to 180°C and the reaction time is 20 h to 28 h.
[0038] It should be noted that the temperature of the first stirring can be 50℃, 60℃, or 70℃, and the duration can be 20min, 30min, or 40min. This invention can further employ stirring at 60℃ for 30min to fully dissolve vanadium salt and thioacetamide under light-protected conditions, eliminating localized solute concentration imbalances and preventing the formation of localized impurity crystals. Additionally, the temperature of the first stirring can be 20℃, 30℃, or 40℃, and the duration can be 0.5h, 1h, or 2h. This invention can further select stirring at 30℃ for 1h, where the low temperature slowly changes the system polarity, gently inducing the directional precipitation of one-dimensional crystal nuclei and preventing rapid nucleation from disrupting the anemone morphology.
[0039] In some specific examples, in the preparation method of anemone-shaped vanadium tetrasulfide in the above magnesium-vanadium tetrasulfide battery, in step (3), the temperature of the solvothermal reaction is 150°C to 180°C and the reaction time is 20h to 28h.
[0040] It should be noted that the temperature of the solvothermal reaction can be 150℃, 155℃, 160℃, 165℃, 170℃, 175℃ or 180℃, etc., and the duration can be 20h, 22h, 24h, 26h or 28h, etc.; below 150℃, the sulfurization reaction is insufficient and the nanorods are short; above 180℃, the crystals become excessively coarse and the pores disappear; in this invention, it is possible to select 160℃ for 24h to form a complete anemone-shaped pure phase VS4.
[0041] In some specific examples, in the preparation method of anemone-shaped vanadium tetrasulfide in the above magnesium-vanadium tetrasulfide battery, in step (3), after the solution C undergoes a solvothermal reaction, it is centrifuged, the precipitate is washed, and dried to obtain anemone-shaped vanadium tetrasulfide powder; wherein, the washing includes: washing with deionized water and anhydrous ethanol at least three times in sequence; and / or drying is vacuum drying, the drying temperature is 60°C to 100°C, and the drying time is 10h to 14h.
[0042] It should be noted that the residual soluble sulfur salts and NMP organic solvent impurities in the solvothermal products will continuously cause electrolyte decomposition and aggravate self-discharge if the electrodes are directly prepared. Deionized water is used to wash away water-soluble ionic impurities, and anhydrous ethanol is used to replace and remove residual organic solvents. Each washing is repeated ≥3 times for thorough purification. The vacuum drying temperature can be selected from 60℃, 80℃ or 100℃, and the duration can be 10h, 12h or 14h.
[0043] In some specific examples, in the above-mentioned magnesium-vanadium tetrasulfide batteries, the Grignard reagent-based magnesium battery electrolyte is selected from APC electrolyte (phenyl magnesium chloride-aluminum trichloride / tetrahydrofuran complex electrolyte), phenoxy magnesium chloride-aluminum chloride complex electrolyte, or magnesium aluminum chloride complex electrolyte; and / or the solvent of the non-aqueous electrolyte is selected from one or more combinations of tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, or tetraethylene glycol dimethyl ether.
[0044] It should be noted that the Grignard-type magnesium electrolyte in this invention has excellent chemical compatibility with the metallic magnesium anode, will not severely corrode the magnesium substrate, and can stably dissociate free Mg. 2+ The dimethyl ether series and THF ether solvents are selected, which have a wide electrochemical stability window, low viscosity, and high magnesium ion conductivity, making them suitable for the VS4 positive electrode charge and discharge potential range. THF alone has a low boiling point and is prone to volatilization under high temperature conditions. The combination of polyether solvents can balance viscosity, boiling point, and ion conduction performance, making it suitable for energy storage conditions of different rates and temperatures.
[0045] In some specific examples, in the above-mentioned magnesium-vanadium tetrasulfide battery, the concentrations of electrolyte additives acting on the positive electrode and electrolyte additives acting on the negative electrode in the non-aqueous electrolyte are independently 0.1 mol / L to 0.5 mol / L.
[0046] It should be noted that the concentration of the electrolyte additive (for either the positive or negative electrode) can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, or 0.5 mol / L, etc. Concentrations below 0.1 mol / L result in weak interface regulation and interlayer pore-expanding effects, failing to improve magnesium ion kinetics. Concentrations above 0.5 mol / L lead to a significant increase in overall electrolyte viscosity, a decrease in ionic conductivity, and a deterioration in rate performance. This invention preferably uses 0.2 M PY14Cl and 0.2 M indium chloride additives, balancing interface modification and ion transport efficiency, resulting in optimal long-cycle performance.
[0047] In some specific examples, the above-mentioned magnesium-vanadium tetrasulfide battery also includes a conductive agent and a binder in the positive electrode. The conductive agent is one or more combinations of conductive carbon black, conductive graphite, carbon nanotubes or graphene, and the binder is polyvinylidene fluoride (PVDF). The mass ratio of the magnesium-based battery positive electrode material, the conductive agent and the binder is (6-8):(1-3):1.
[0048] It should be noted that the mass ratio of the magnesium-based battery cathode material, conductive agent, and binder is (6-8):(1-3):1, such as 6:3:1, 7:2:1, or 8:1:1. It should be understood that the conductive agent can be any known battery conductive agent in the art, such as conductive carbon black, conductive graphite, conductive carbon fiber, conductive carbon nanotubes, and conductive graphene; the binder can be any known battery binder in the art, such as PVDF (polyvinylidene fluoride), PVA (polyvinyl alcohol), CMC (sodium carboxymethyl cellulose), PTEF (polytetrafluoroethylene), PP (polyethylene hydrocarbons), fluorinated rubber, polyurethane, or SBR rubber.
[0049] In some specific examples, in the above-mentioned magnesium-vanadium tetrasulfide battery, the negative electrode is a magnesium foil negative electrode sheet or a magnesium alloy negative electrode sheet, and the magnesium alloy is selected from one or more combinations of AZ31 magnesium alloy, magnesium gadolinium alloy or magnesium cerium alloy.
[0050] It should be noted that pure magnesium foil has high magnesium ion conductivity, but it is prone to dendrite formation during long cycles; AZ31, gadolinium magnesium, and magnesium-cerium alloys can inhibit dendrite formation and improve the cycle stability of the negative electrode. They can be used alone or in combination according to cycle life requirements; the negative electrode is polished and ultrasonically removed before use to further improve the interfacial ion conduction efficiency.
[0051] To better understand the present invention, specific examples are provided below to further illustrate the content of the present invention, but the content of the present invention is not limited to the examples below.
[0052] Preparation Example
[0053] Example 1
[0054] (1) Preparation of anemone-shaped VS4 (vanadium tetrasulfide) cathode material
[0055] 1) Weigh 0.6g of ammonium metavanadate (NH4VO3) powder and 1.8g of thioacetamide (C2H5NS), dissolve them in 30mL of N-methylpyrrolidone (NMP) to obtain solution A.
[0056] 2) Place solution A in a 60°C water bath and stir with an electromagnetic stirrer for 30 minutes under light-protected conditions; then add 30 mL of anhydrous ethanol to solution A to obtain solution B, and continue electromagnetic stirring at 30°C for 1 hour.
[0057] 3) Transfer solution B to a 100 mL reaction vessel and carry out a solvothermal reaction at 160°C for 24 hours.
[0058] 4) After the reaction is complete, the product is washed three times by centrifugation using deionized water and anhydrous ethanol respectively.
[0059] 5) The washed product was vacuum dried at 80°C for 12 hours to obtain anemone-shaped vanadium tetrasulfide powder.
[0060] (2) Preparation of positive electrode sheet
[0061] 1) The anemone-shaped vanadium tetrasulfide powder, conductive carbon black and binder PVDF prepared above are dispersed in N-methylpyrrolidone solvent at a mass ratio of 8:1:1. After grinding with a mortar and pestle, the mixture is stirred for 4 hours to obtain a uniformly mixed positive electrode slurry.
[0062] 2) The positive electrode slurry is uniformly coated on a hydrophobic conductive carbon cloth with a diameter of 14 mm. After being vacuum dried at 80°C overnight, the working positive electrode sheet is obtained. The loading of active material on the positive electrode sheet after drying is controlled between 1.5 mg and 2 mg.
[0063] (3) Pretreatment of negative electrode sheet
[0064] Pure magnesium foil is cut into circular pieces with a diameter of 16mm. After being sanded and ultrasonically cleaned to remove the surface passivation film, it is placed in an argon glove box for later use.
[0065] (4) Preparation of electrolyte
[0066] In an argon glove box, 4 mL of 2 M PhMgCl / THF solution (phenyl magnesium chloride / tetrahydrofuran solution) was added to 6 mL of THF solvent (tetrahydrofuran), followed by the slow addition of 0.553 g of AlCl3 powder; then 0.2 M 1-butyl-1-methylpyrrolidine chloride (PY14Cl) and 0.2 M indium chloride were added, and the mixture was stirred thoroughly for 12 hours to obtain the APC-PY14Cl / THF electrolyte.
[0067] (5) Battery assembly
[0068] Inside the argon glove box, a gasket, a spring, a negative electrode plate, and a separator are placed sequentially on the negative electrode shell. Then, electrolyte is added until it just wets the separator. The positive electrode plate is then placed on top, and the positive electrode shell is covered before sealing.
[0069] Example 2
[0070] Example 2 is largely the same as Example 1, except that in step (2) of Example 2, the mass ratio of anemone-shaped vanadium tetrasulfide powder, conductive carbon black and binder PVDF in the preparation of the positive electrode is 6:3:1, and the other steps are the same as in Example 1.
[0071] Example 3
[0072] Example 3 is largely the same as Example 1, except that in step (4) of Example 3, the concentration of 1-butyl-1-methylpyrrolidine chloride added in the preparation of the electrolyte is 0.1M, and the other steps are the same as in Example 1.
[0073] Example 4
[0074] Example 3 is largely the same as Example 1, except that in step (4) of Example 4, the concentration of 1-butyl-1-methylpyrrolidine chloride added is 0.5M in the preparation of the electrolyte, and the other steps are the same as in Example 1.
[0075] Example 5
[0076] Example 3 is largely the same as Example 1, except that in step (4) of Example 4, the concentration of indium chloride added is 0.1M in the preparation of the electrolyte, and the other steps are the same as in Example 1.
[0077] Example 6
[0078] Example 3 is largely the same as Example 1, except that in step (4) of Example 4, the concentration of indium chloride added is 0.5M in the preparation of the electrolyte, and the other steps are the same as in Example 1.
[0079] Comparative Example 1
[0080] Comparative Example 1 is largely the same as Example 1, except that in step (4) of Comparative Example 1, 1-butyl-1-methylpyrrolidine chloride was not added in the preparation of the electrolyte. The other steps are the same as in Example 1.
[0081] Characterization test
[0082] The anemone-shaped vanadium tetrasulfide powder obtained in Example 1 was subjected to X-ray diffraction analysis. The results are as follows: Figure 1 As shown, the results indicate that the diffraction peaks of the prepared anemone-shaped vanadium tetrasulfide powder are in good agreement with the standard peaks of vanadium tetrasulfide monoclinic crystals (JCPDS No. 72-1294), and the diffraction peaks are relatively sharp, proving that the product has good crystallinity.
[0083] In addition, the anemone-like vanadium tetrasulfide powder obtained in Example 1 was analyzed by transmission electron microscopy. The results are as follows: Figure 2As shown, the results indicate that the prepared anemone-like vanadium tetrasulfide powder is a structure resembling anemones, formed by the stacking of divergently growing nanorods. Each nanorod has a diameter of approximately 10 nm to 30 nm and a length of approximately 1 μm to 2 μm. This anemone-like structure allows each nanorod to be tightly anchored together, forming a relatively stable structure. Furthermore, the divergent growth at the ends of the nanorods increases the specific surface area of the material, providing more electrochemically active sites.
[0084] Performance testing
[0085] After the button cells assembled in Examples 1, 2, 3, 4, 5, 6, and Comparative Example 1 were left to stand for 8 hours, they were tested using a Newway battery tester. The test current was 50 mA·g. -1 and 2A·g -1 The charge / discharge cutoff voltage is 0.35V to 2V, and the test temperature is 25℃ to 30℃.
[0086] (1) Constant current charge-discharge test (50mA·g) -1 )
[0087] The coin cells assembled in Example 1 and Comparative Example 1 were subjected to a temperature of 50 mA·g. -1 The constant current charge-discharge curves at current density are as follows: Figure 3 and Figure 5 As shown, the results indicate that the coin cell assembled in Example 1 performs well at 50 mA·g. -1 At a current density of [value missing], the actual discharge specific capacity is as high as 250 mAh·g. -1 ( Figure 3 The discharge specific capacity of the coin cell assembled in Comparative Example 1 was significantly lower than that in Example 1. Figure 4 ).
[0088] (2) Cyclic performance test (2A·g) -1 )
[0089] The coin cells assembled in Example 1 and Comparative Example 1 were tested at 2 A·g -1 The cycling performance curves at current densities are as follows: Figure 4 and Figure 6 As shown, the results indicate that the coin cell assembled in Example 1 performs well at 2 A·g. -1 After 25,000 cycles at high current density, the capacity retention rate is as high as 61.6%. Figure 5 The cycle stability of the coin cell assembled in Comparative Example 1 was significantly worse than that in Example 1. Figure 6 ).
[0090] The battery performance of Examples 1 to 6 was compared with that of Comparative Example 1, and the results are shown in Table 1.
[0091] Table 1 Comparison of battery performance between Examples 1 to 6 and Comparative Example 1
[0092] Example 1 250 mAh g -1 ]] 25,000 laps 61.6% Example 2 248 mAh.g -1 ]] 25,000 laps 60.8% Example 3 223 mAh·g -1 ]] 25,000 laps 57.7% Example 4 <![CDATA[200 mAh·g -1 ]]> 20,000 laps 51.9% Example 5 240 mAh-g -1 ]] 8000 laps 48.7% Example 6 <![CDATA[197mAh·g -1 ]]> 10,000 laps 52.3% Comparative Example 1 <![CDATA[117mAh·g -1 ]]> 20,000 laps 50.2%
[0093] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A long-life magnesium-vanadium tetrasulfide battery, comprising a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte, characterized in that, The positive electrode contains anemone-shaped vanadium tetrasulfide, which is formed by multiple nanorods that aggregate at the root and diverge at the tail. The nanorods have a diameter of 10 nm to 30 nm and a length of 1 μm to 2 μm. The non-aqueous electrolyte includes a magnesium battery electrolyte and electrolyte additives that act on the positive and negative electrodes. The magnesium battery electrolyte is a Grignard reagent-based magnesium battery electrolyte. The electrolyte additives include electrolyte additives that act on the positive electrode and electrolyte additives that act on the negative electrode. The electrolyte additive that acts on the positive electrode is selected from one or more combinations of 1-butyl-1-methylpyrrolidine chloride (PY14Cl), 1-butyl-1-methylpyrrolidine onium bromide (BMPyrrBr), hexadecyltrimethylammonium chloride (CTACl), or tetrabutylammonium chloride (TBACl). The electrolyte additive that acts on the negative electrode is indium chloride.
2. The magnesium-vanadium tetrasulfide battery according to claim 1, characterized in that, The specific surface area of anemone-shaped vanadium tetrasulfide is 20 m². 2 / g~50m 2 / g.
3. The magnesium-vanadium tetrasulfide battery according to claim 1 or 2, characterized in that, Methods for preparing anemone-shaped vanadium tetrasulfide include: (1) Dissolve ammonium metavanadate in N-methylpyrrolidone to obtain solution A; dissolve thioacetamide in anhydrous ethanol to obtain solution B; (2) Mix solution A with solution B to obtain solution C; (3) The solution C was subjected to a solvothermal reaction to obtain anemone-shaped vanadium tetrasulfide.
4. The magnesium-vanadium tetrasulfide battery according to claim 3, characterized in that, The mass ratio of ammonium metavanadate to thioacetamide is 1:(2-4); and / or The volume ratio of N-methylpyrrolidone to anhydrous ethanol is 1:(0.8 to 1.2).
5. The magnesium-vanadium tetrasulfide battery according to claim 3, characterized in that, Step (2) includes: mixing solutions A and B under a first stirring, followed by a second stirring to obtain solution C; the temperature of the first stirring is 50°C to 70°C, and the time is 20 min to 40 min; the temperature of the second stirring is 20°C to 40°C, and the time is 0.5 h to 2 h; and / or In step (3), the temperature of the solvothermal reaction is 150°C to 180°C, and the reaction time is 20h to 28h.
6. The magnesium-vanadium tetrasulfide battery according to claim 3, characterized in that, In step (3), after solution C undergoes a solvothermal reaction, it is centrifuged, the precipitate is washed, and dried to obtain anemone-shaped vanadium tetrasulfide powder; wherein, Washing includes: washing at least three times each with deionized water and anhydrous ethanol; and / or The drying process is vacuum drying, with a drying temperature of 60℃~100℃ and a drying time of 10h~14h.
7. The magnesium-vanadium tetrasulfide battery according to claim 1, 2, 4, 5 or 6, characterized in that, The Grignard reagent-based magnesium battery electrolyte is selected from phenyl magnesium chloride-aluminum trichloride / tetrahydrofuran complex electrolyte, phenoxy magnesium chloride-aluminum chloride complex electrolyte, or magnesium aluminum chloride complex electrolyte.
8. The magnesium-vanadium tetrasulfide battery according to claim 1, 2, 4, 5 or 6, characterized in that, The solvent for the non-aqueous electrolyte is selected from one or more combinations of tetrahydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, or tetraethylene glycol dimethyl ether.
9. The magnesium-vanadium tetrasulfide battery according to claim 1, 2, 4, 5 or 6, characterized in that, The concentrations of the electrolyte additives acting on the positive electrode and the electrolyte additives acting on the negative electrode in the non-aqueous electrolyte are independently 0.1 mol / L to 0.5 mol / L.
10. The magnesium-vanadium tetrasulfide battery according to claim 1, 2, 4, 5 or 6, characterized in that, The positive electrode also includes a conductive agent and a binder. The conductive agent is one or more combinations of conductive carbon black, conductive graphite, carbon nanotubes, or graphene, and the binder is polyvinylidene fluoride (PVDF). The mass ratio of the magnesium-based battery positive electrode material, conductive agent, and binder is (6-8):(1-3):1; and / or The negative electrode is a magnesium foil negative electrode sheet or a magnesium alloy negative electrode sheet, wherein the magnesium alloy is selected from one or more combinations of AZ31 magnesium alloy, magnesium gadolinium alloy or magnesium cerium alloy.
